2014
DOI: 10.1186/1756-0500-7-757
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to Sindbis virus infection of neural progenitors derived from human embryonic stem cells

Abstract: BackgroundSindbis virus (SINV) causes age-dependent encephalitis in mice, and therefore serves as a model to study viral encephalitis. SINV is used as a vector for the delivery of genes into selected neural stem cell lines; however, the toxicity and side effects of this vector have rarely been discussed. In this context, we investigated the cellular responses of human embryonic stem cell (hESCs) derived neural progenitors (hNPCs) to SINV infection by assessing susceptibility of the cells to SINV infection, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(45 reference statements)
2
1
0
Order By: Relevance
“…Its downregulation during ONNV infection was consistent with a previous report for SINV in vitro in human neural progenitor (hNPC) cells [65], and its upregulation occurred only with TAB. The downregulation of STAT3 gene expression was also established in vitro for SINV in hNPC [65], but our data were inconclusive. The NLRP3/caspase-1 pathway favors the strong pro-inflammatory mediator release (IL-18 and IL-1β) and pyroptosis [66] and is related to the severity of the alphavirus infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Its downregulation during ONNV infection was consistent with a previous report for SINV in vitro in human neural progenitor (hNPC) cells [65], and its upregulation occurred only with TAB. The downregulation of STAT3 gene expression was also established in vitro for SINV in hNPC [65], but our data were inconclusive. The NLRP3/caspase-1 pathway favors the strong pro-inflammatory mediator release (IL-18 and IL-1β) and pyroptosis [66] and is related to the severity of the alphavirus infection.…”
Section: Discussionsupporting
confidence: 92%
“…The MAPK pathway is involved in lifecycle of the cell and the inflammatory responses [ 64 ], and it was reported that CHIKV induced MAPK expression in human osteosarcoma (HOS) cells [ 45 ]. Its downregulation during ONNV infection was consistent with a previous report for SINV in vitro in human neural progenitor (hNPC) cells [ 65 ], and its upregulation occurred only with TAB. The downregulation of STAT3 gene expression was also established in vitro for SINV in hNPC [ 65 ], but our data were inconclusive.…”
Section: Discussionsupporting
confidence: 91%
“… 11 We also confirmed the consequences of ER stress in hNS1 cells and found it as an executioner phenomenon leading to stem cell apoptosis. Evidences indicate neural stem cell death in many other cases of viral infection like Zika virus reducing viable number of cortical hNPCs, 12 Sindbis virus inducing apoptosis in hNPCs 13 and Cytomegalovirus promoting apoptosis in NSPCs following ER stress. 14 Zika virus is also reported to infect neural progenitors resulting in microcephaly.…”
mentioning
confidence: 99%